Giving meaning to Ellenberg nutrient values: National Forest Soil Inventory yields frequency‐based scaling. Issue 1 (25th October 2016) - Ewald, Jörg; Ziche, Daniel
Abstract: Questions: Ellenberg nutrient values based on indicator plant species composition of vegetation plots (mN) are widely used to measure temporal and spatial patterns of nutrient deficiency and eutrophication. The widespread use is in contrast to the lack of direct calibration against soil chemical proxies of nutrient availability. Lack of calibration and range contraction due to averaging of a bounded ordinal scale hinder the interpretation of mN across studies. Based on a large set of concomitant vegetation–soil data we asked: (1) which is the best single soil predictor of mN, (2) which combination of soil variables best explains mN; and (3) can a meaningful relative scale of mN be provided for comparative purposes? Location: Forests in Germany, sampled in a systematic 8 km × 8 km grid. Methods: The German National Forest Soil Inventory (NFSI) provides a large, representative sample of joint soil and vegetation plots, which were additionally intersected with modelled background N deposition. Values of mN of vegetation plots were related to measured 36 soil and three deposition variables by correlation and multiple regression. The distribution of mN was partitioned based on quantiles. Results: In NFSI mN was most closely related to the C/N ratio of the topsoil ( r ² = 0.31). Multiple analysis regression showed that soil acidity, soil P and K, humus quality and deposition were complementary predictors (multiple r ² = 0.47) of mN. Conclusions: Values of mN are moderately, but consistently, related to measurable chemical properties of forest soils. The 10, 30, 70 and 90% quantiles of the frequency distribution of mN in the NFSI data are proposed to define a relative scale of macronutrient availability in forest soils, distinguishing very oligotrophic (mN < 3.38), oligotrophic (3.38–4.8), mesotrophic (4.80–5.75), eutrophic (5.75–6.21) and highly eutrophic (>6.21) sites, which broadly correspond to conventional classes of C/N ratio used in forest site mapping. This proposed five‐class trophic scale can be used to compare mN and its trends across studies in forest vegetation of Central Europe. Abstract : The National Inventory of Germany's forest soils and vegetation yields a relative scaling of the widely used Ellenberg values for nutrients. Among all soil variables they are most closely related to C/N ratio of the topsoil.